Yiddish in the Andes. Unbearable distance, devoted activists and building Yiddish culture in Chile. Issue 4 (2nd October 2019) - Kałczewiak, Mariusz
ABSTRACT: This article elucidates the efforts of Chilean-Jewish activists to create, manage and protect Chilean Yiddish culture. It illuminates how Yiddish cultural leaders in small diasporas, such as Chile, worked to maintain dialogue with other Jewish centers. Chilean culturists maintained that a unique Latin American Jewish culture existed and needed to be strengthened through the joint efforts of all Yiddish actors on the continent. Chilean activists envisioned a modern Jewish culture informed by both Eastern European influences and local Jewish cultural production, as well as by exchanges with non-Jewish Latin American majority cultures.